LGPD Framework: An Implementation and Compliance Guide for Technology Areas - Carturan, Sara B. O. G.; Matsui, Beatriz M. A.; Goya, Denise H. (Anais do Seminário Integrado de Software e Hardware (SEMISH), 2022)
Considering the unrestrained consumption of personal data, the LGPD came to protect and regulate the treatment of data, whether digital or physical. Due to the lack of technical guides to interpret the LGPD and apply it in the technology area, a gap arises that impacts IT management. This paper proposes a conceptual framework composed of domains and components to facilitate the LGPD interpretation and implementation by technology areas. The framework was mainly inspired by the essential principles of COBIT 2019 and DevOps, which transform a concept into a practical method of understanding and implementation. The LGPD framework will guide organizations to be compliant in a shorter time and to provide cultural and behavioral changes.